Determinants of Chronic Total Occlusion in Patients With Peripheral Arterial Occlusive Disease. (February 2017) - Hamur, Hikmet; Onk, Oruc Alper; Vuruskan, Ertan; Duman, Hakan; Bakirci, Eftal Murat; Kucuksu, Zafer; Degirmenci, Husnu; Buyuklu, Mutlu; Topal, Ergun
Chronic total occlusion (CTO) is a common finding in 40% of the patients with peripheral arterial disease (PAD). The aim of this study was to investigate the determinants of CTO in patients with PAD. The study included a total of 211 nonanemic patients with PAD. All patients were categorized according to the Fontaine classification. In lower extremity angiography cohorts, CTO − patients were designated as group 1 and CTO + patients were designated as group 2. Patients with CTO had significantly higher red cell distribution width (RDW), neutrophil–lymphocyte ratio, uric acid, and high-sensitivity C-reactive protein compared to patients without CTO ( P ≤ .001, P = .036, P ≤ .001, and P = .015, respectively). Albumin, total bilirubin, and direct bilirubin were significantly lower in the patients with CTO compared to patients without CTO ( P = .023, P ≤ .001, and P = .049, respectively). Multivariate logistic regression analysis showed that RDW, uric acid, and total bilirubin were independent predictors of CTO in patients with PAD. We demonstrated that increased RDW and uric acid levels and lower total bilirubin values were independently associated with CTO in patients with PAD.